FINANCIAL PRIORITIES OF ECOLOGICAL SAFETY SUPPORTING (BASED ON THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT) (Economics and region, 2017)
UDC 330 : 502.57 : 504Hanna Obikhod, PhD (Economics), associate professor, senior researcher. Alla Omelchenko, PhD (Economics), researcher. Public Institution «Institute for Environmental Economics and Sustainable Development of NAS of Ukraine». Financial Priorities of Ecological Safety Supporting (based on the principles of sustainable development). The authors distinguished the need for further development of the funding system of guaranteeing ecological safety is established and a conceptual scheme of approaches to defining its priorities. There are described in the article the areas of optimization of financial flows in view of continued decentralization processes. These areas include: improvement of budget funds use (at national and regional levels) in environmental and natural and technogenic safety area; monitoring of funding; focus on balancing expenditures and revenues to the regional budget; strengthening of fiscal capacity of the latter; paradigm shift of financial support for environmental security of the region; development of environmental insurance. Possibilities for improving the financing system in the field of safety based on the potential involvement of EU structural funds, especially The Cohesion Fund, which is not currently available in Ukraine, are grounded.This structure makes investments through appropriate mechanisms to overcome territorial disparities, including the environmental field. Special attention should be paid to the developed technique of evaluating the effectiveness of the use of its funds by indicators of the environmental state, energy to overcome the impact of climate change, the development of trans-European transport network (TEN-T).Key words: ecological safety, financial priorities, reserve fund, sustainable development.